AI-Mediated speaking practice in EFL contexts: Exploring students' perceptions of Flow Speak - Rizka Fikrotul Azizah; Tiyas Saputri; Nailul Authar (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2026)
This study explored EFL students’ perceptions of using Flow Speak, an artificial intelligence (AI)-based application, for English speaking practice. Using a qualitative descriptive design, data were collected through open-ended questionnaires from 20 students in an English Language Education Program who had used Flow Speak for one to five months. The data were analyzed using thematic analysis. The findings revealed five major themes: speaking difficulties before using Flow Speak, experiences with the application, perceived improvements in speaking skills, benefits for autonomous learning, and challenges encountered. Participants reported that Flow Speak provided real-time feedback, repeated speaking opportunities, and a low-pressure learning environment that supported speaking practice. They also perceived improvements in vocabulary use, pronunciation awareness, confidence, and fluency, particularly among students with longer experience using the application. In addition, participants highlighted the flexibility of independent practice and the role of immediate feedback in supporting learner autonomy. However, challenges related to internet connectivity, speech-recognition accuracy, and the lack of authentic human interaction were also identified. The findings suggest that AI-assisted speaking applications may serve as useful supplementary tools for self-directed speaking practice, while complementing rather than replacing human-mediated language learning experiences.